خلع میں حکمِ حاکم کی حیثیت: فقہ جعفری کا مطالعہ (Al-Qamar, 2020)
This article studies the status of the order of the ruler for Khulʻ in Jaʻfarī Jurisprudence. Khulʻ (a form of divorce initiated by a wife) is one of the reasons for separation of husband and wife. It is realized at the time when the wife hates her husband and wants to be free from the marital relationship by giving him some money (property). The question arises that as soon as the spouses agree on the money and the money (property) is exchanged, the separation will happen automatically, or is it necessary to approach to the ruler of Sharīʻah to end the marital relationship? According to the Jurists separation will not be achieved automatically by paying money (property). However, there are two theories on whether or not to approach the ruler of Sharīʻah for Khulʻ. This article supports the opinion of the jurists who consider it necessary to approach the ruler of Sharīʻah for Khulʻ.
Keywords: Khulʻ; ruler; Jaʻfarī Jurisprudence; opinions